Smart Economy, Accountability, and Well-Being: Evidence from MSMEs Income Performance - Zakiyah, Rahayu Dewi; Rachmawati, Emi (InFestasi, 2025)
The growth of the online (internet)-based commerce world, also known as e-commerce, has grown very rapidly in the last twenty years. With the rapid development of technology, patterns and systems in economic development continue to change. Technological advances economic actors who own micro, small and medium enterprises (MSMEs) cannot only produce a product, but must also adapt and apply technological development to their economic activities. This study aims to find out how the role of smart economy towards effective accountability and well-being in increasing the income of MSME entrepreneurs. This type of research is qualitative research using primary data. The data collection technique used is the method of observation, interviews, and documentation. The results of the study show that the existence of the smart economy concept will encourage the community, especially in the field of MSMEs to further develop their economy with a digitalization system by utilizing technology and telecommunication will maximize performance and accountability, well being (prosperity) in running a business for MSME actors.